2021
DOI: 10.3390/vaccines9060665
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy in a Representative Education Sector Population in Qatar

Abstract: Even though vaccination programs have now started in earnest across the globe and in Qatar, vaccine hesitancy remains a barrier to effectively tackling the pandemic. Many factors influence willingness to take vaccines including safety, efficacy, and side effects. Given their proximity to research and education, university students and employees represent an interesting cohort in which to investigate vaccine hesitancy. The aim of this study was to assess the attitudes of Qatar University employees and students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 26 publications
4
48
3
Order By: Relevance
“…Overall, 73.3% of the Czech universities' students participating in this study were willing to receive COVID-19 vaccines whenever possible (vaccine accepting group); on the other hand, 19.3% were unwilling to get vaccinated (vaccine-resistant group), and only 7.4% were hesitant about COVID-19 vaccination (vaccine-hesitant group). The current acceptance level of Czech students is higher than what was reported in Qatar (62.6%), France (58%), USA (50.6%), and Jordan (34.9%), and lower than what was reported initially in Italy (86.1%) [47][48][49][50][51].…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Overall, 73.3% of the Czech universities' students participating in this study were willing to receive COVID-19 vaccines whenever possible (vaccine accepting group); on the other hand, 19.3% were unwilling to get vaccinated (vaccine-resistant group), and only 7.4% were hesitant about COVID-19 vaccination (vaccine-hesitant group). The current acceptance level of Czech students is higher than what was reported in Qatar (62.6%), France (58%), USA (50.6%), and Jordan (34.9%), and lower than what was reported initially in Italy (86.1%) [47][48][49][50][51].…”
Section: Discussioncontrasting
confidence: 58%
“…Al-Mulla et al 2021 found that HCS (80.6%) in Qatar had significantly higher levels of COVID-19 vaccine acceptance ( χ 2 = 5.40, Sig. = 0.02) compared to non-HCS (61%) [ 47 ]. Similarly, Polish HCS (91.99%), French HCS (50.8%), and Jordanian HCS (43.5%) were more vaccine accepting than Polish non-HCS (59.42%), French non-HCS (32.3%) and Jordanian non-HCS (24%) [ 37 , 48 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…for similar vaccines to establish their efficacy and side effects. In Iran 39 and Qatar, 43 the intention to be vaccinated was higher among those with greater belief in the vaccines' efficacy.…”
Section: Perception Of Vaccine Efficacymentioning
confidence: 92%
“…However, some recent studies indicate that belief in the importance of other adult immunisations may be positively associated with COVID-19 vaccine acceptance. One study in Qatar 43 revealed that participants who believed it was important to take the annual influenza vaccination were more likely to get vaccinated against COVID-19. A situational analysis of Syria 18 suggested that routine immunisation might be a strong predictor of COVID-19 vaccine acceptance.…”
Section: Perception Of Routine Immunisationmentioning
confidence: 99%
See 1 more Smart Citation